2020
DOI: 10.1016/j.ejmech.2020.112711
|View full text |Cite
|
Sign up to set email alerts
|

The development of Coronavirus 3C-Like protease (3CLpro) inhibitors from 2010 to 2020

Abstract: This review fully describes the coronavirus 3CL pro peptidomimetic inhibitors and nonpeptidic small molecule inhibitors developed from 2010 to 2020. Specifically, the structural characteristics, binding modes and SARs of these 3CL pro inhibitors are expounded in detail by division into two categories: peptidomimetic inhibitors mainly utilize electrophilic warhead groups to covalently bind the 3CL pro Cys145 residue and thereby achieve irrever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 105 publications
0
135
0
Order By: Relevance
“…Inhibitors possessing sub-µM affinity to M pro typically mimic Gln by introducing a lactam functionality as their P1 substituent in order to engage His163 in a hydrogen bond. 39 Telaprevir features a hydrophobic norvaline substituent in P1 position that cannot make hydrogen bonds in subsite S1. Compared to the ligand-free structure, inhibitor binding leads to the recruitment of a water molecule into subsite S1.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors possessing sub-µM affinity to M pro typically mimic Gln by introducing a lactam functionality as their P1 substituent in order to engage His163 in a hydrogen bond. 39 Telaprevir features a hydrophobic norvaline substituent in P1 position that cannot make hydrogen bonds in subsite S1. Compared to the ligand-free structure, inhibitor binding leads to the recruitment of a water molecule into subsite S1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the lung tropism of 9 is a favourable target organ feature. A mouse lung drug inhalation model showed that 9 is well tolerated without adverse reactions; hence, lung inhalation is the appropriate method for the administration of 9 [ 41 ].
Fig.
…”
Section: Coronavirus Non-structural Protein Inhibitorsmentioning
confidence: 99%
“…It was found that NPs/SMs are a rich source of drug potential leads against coronaviruses due to their pronounced structural diversity and complexity. Several compilations of pre-2020 findings on NPs/SMs with activity against coronaviruses were recently reported, some of which could serve as leads for the development of new drugs [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Among the identified molecules the majority is represented by NPs ( Figure 2 a) and most of them have been found as inhibitors of SARS-CoV ( Figure 2 b).…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%